2018
DOI: 10.22159/ajpcr.2018.v11i11.27199
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Video Laryngoscopy and Fiberoptic for Airway Management in a Patient With Fixed Cervical Spine

Abstract: Airway management may be difficult in patients with fixed cervical spine who have undergone previous spine surgery. Among the various techniques, fiber-optic intubation is a preferred method for securing the airway in such situation. However, it has some limitations also like identification of landmarks, especially in a case of distorted anatomy of the airway. To overcome this inadequacy, we used video laryngoscopy as a complement, to guide the tip of bronchoscope beneath the epiglottis into the trachea and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Case reports also observed successful intubation occurring with various combinations of techniques (Category B4-B evidence). 447–468…”
Section: Anticipated Difficult Airway Managementmentioning
confidence: 99%
“…Case reports also observed successful intubation occurring with various combinations of techniques (Category B4-B evidence). 447–468…”
Section: Anticipated Difficult Airway Managementmentioning
confidence: 99%
“…A study by Lenhardt et al 42 reported that this technique has a higher success rate of intubation in the difficult airway, especially during intubations with in-line stabilization. Moda et al 43 also published a case report of successfully intubating a patient with a difficult airway of the fixed C-spine with distorted anatomy. This is a relatively new technique, and research is still going on to determine the advantage of this technique over other techniques.…”
Section: Videolaryngoscope-assisted Fiberoptic Bronchoscopymentioning
confidence: 99%